. Evaluación de 3 niveles de pollstress-pak en el crecimiento de cerdos duroc x largewhite en la uai porcina de la Espoch, cantón Riobamba - Pilataxi Pilataxi, María Teresa (2022)
In the current research, Pollstress-pak different levels (0.1%; 0.2%; 0.3% were used in the growth phase pigs’ nutrition, due to the additive improves the intestinal tract bacterial population balance, the product was added to the pigs’ diet in order to evaluate each set level effect, about weight gaining, feed consumption, feed conversion, and cross height. This work was carried out at Escuela Superior Politécnica de Chimborazo Swine Research Academic Unit, where we worked with 16 male piglets from 71 days old Duroc x large white crossing, with an initial average weight of 30.07 kg, the same ones that were distributed completely randomly throug the completely random block system, with four treatments and four repetitions, with a total of sixteen experimental units. The experimental results showed statistical differences and it was observed that Pollstress-pak along with the balanced had great effects at big production at different levels, but it was determined that Pollstress-pak best level was 0.3 % corresponding to T3 that outperformed other treatments with 76.11 kg final weight, with the best feed conversion of 2.25 and the biggest overall weight gain of 46.11 kg, with this it was verified that T3 was which had the best performance. To demonstrate diets quality, the balanced bromatological and the used additive analysis was made, whose results indicated that diets had nutritional components in adequate percentages as required by piglets for their optimal growth and development, bromatological examinations of pig feces were also carried out to determine the fed diet apparent digestibility, that is, the amount of the nutrient that was assimilated by the animal. Similarly, to verify possible changes in blood parameters in pigs due to the ingestion of these diets, metabolic analysis was performed (blood chemistry), with which it was possible to affirm that pigs didn’t have any liver or kidney damage.